Rättssäkerhet eller rätt så osäkert? En granskning av miljöprövningsdelegationen utifrån kraven på rättssäkerhet - Mommers,Nils (2025)
The Environmental Assessment Delegation (MPD) is a decision-making body administratively organised within the County Administrative Board but is expected to make independent decisions in permit matters. At the same time, the County Administrative Board, formally separate from MPD, may be a party in these matters and is also the regulatory authority. This creates an unclear line between supervision and processing. According to case law from the European Court of Human Rights MPS’s processing may also be regarded as judicial proceedings. This entails high demands on impartiality and independence beyond the requirements of Swedish law. This thesis examines to what degree MPD meet the applicable standards of rule of law according to the European Convention on Human Rights and Swedish administrative law. It also examines to what degree the government report’s proposal to abolish MPD is in accordance with rule of law. Finally, the thesis discusses whether the institutional prerequisites for rule of law for MPD exist. The report proposed the establishment of a new, independent environmental assessment authority. The reasons cited for abolishing MPD included lack of predictability and an unclear division of responsibilities between authorities. This thesis also highlights the meaning of rule of law in permit matters, with a particular focus on the requirement of objective impartiality. Meaning there must be no legitimate doubts regarding the impartiality of the decision-making body. The analysis identifies several deficiencies and reasons for legitimate doubts in the current system. One such issue is the organisational closeness to the County Administrative Board. The proposed regulation is considered to ad- dress many of these deficiencies through the establishment of an independent assessment authority. Finally, it is determined that the current regulation is insufficient for MPD to meet the prerequisites of rule of law.
Keywords: Förvaltningsrätt; miljörätt; miljöprocessrätt; rättssäkerhet